1999
DOI: 10.1111/j.1540-8159.1999.tb00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Brugada‐Like Electrocardiographic Pattern in a Patient With a Mediastinal Tumor

Abstract: We report on a patient with a mediastinal tumor and electrocardiographic findings similar to those described in the Brugada syndrome. This peculiar ECG pattern disappeared after tumor removal, thus suggesting it was probably caused by compression of the right ventricular outflow tract by the mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…The most common ECG findings associated with pectus excavatum are negative P wave in lead V1, which is fairly normalized after sternal turnover operation, and incomplete right bundle branch block pattern related to the leftward displacement of the heart (7). Anterior mediastinal tumors could also compress the heart (8, 9), and Tarin et al (10) reported ECG findings similar to the Brugada syndrome pattern, but no angina-like ST segment changes were noted in those patients. The present patient developed angina-like chest pain and ST segment changes on the ECG.…”
Section: Discussionmentioning
confidence: 99%
“…The most common ECG findings associated with pectus excavatum are negative P wave in lead V1, which is fairly normalized after sternal turnover operation, and incomplete right bundle branch block pattern related to the leftward displacement of the heart (7). Anterior mediastinal tumors could also compress the heart (8, 9), and Tarin et al (10) reported ECG findings similar to the Brugada syndrome pattern, but no angina-like ST segment changes were noted in those patients. The present patient developed angina-like chest pain and ST segment changes on the ECG.…”
Section: Discussionmentioning
confidence: 99%
“…6,22-24,31-33 In a similar way, tumor in the mediastinum could mimic Brugada-type ECG, probably due to compression and displacement of the ventricular wall, causing the RVOT area to be closer to the recording lead position. 37 During deep inspiration, the heart is pulled downward as the diaphragm falls following lung expansion, leading the right precordial leads at conventional lead positions (V1-V3) to be closer to RVOT. This corresponds to the present findings that heart position, evaluated on X-ray, was lower in the deep inspiratory phase than in the expiratory phase.…”
Section: Discussionmentioning
confidence: 99%
“…Right or left bundle branch block, left ventricular hypertrophy 28 Acute myocardial ischemia or infarction 29 Acute myocarditis 30 Right ventricular ischemia or infarction 31 Dissecting aortic aneurysm 32 Acute pulmonary thromboemboli 33 Various central and autonomic nervous system abnormalities 34,35 Heterocyclic antidepressant overdose 36 Duchenne muscular dystrophy 37 Friedreich's ataxia 38 Thiamine deficiency 39,40 Hypercalcemia 41 Hyperkalemia 42 Cocaine intoxication 43,44 Mediastinal tumor compressing RVOT 45 Arrhythmogenic right ventricular dysplasia/cardiomyopathy 24,25 Long-QT syndrome, type 3 11,12 Other conditions that can lead to ST-segment elevation in the right precordial leads…”
Section: Table 2 Abnormalities That Can Lead To St-segment Elevationmentioning
confidence: 99%